Optimization of natural fiber composite parameter using Taguchi approach - Md Yusof, Fauziah; Abd Rahim, Mohd Khairul Hazami; Samsudin, Ahmad Safwan; Mohamad Nor, Nor Hafiez; Ahmad, Zuraida; Halim, Zahurin (Trans Tech Publications, Switzerland, 2016)
Natural fibre composition is a brilliant option for the most widely applied fibre in the composite innovation. The advantages of natural fibre composites are renewable, environmental friendly, low cost, low density, flexibility of usage and tend to decompose (biodegradability). Since there are hundreds fibre that could be utilized in natural fibre composite, optimization in design of experiment is essential in fabricating natural fiber composite. Taguchi’s method is used within this study in which, it can reduce the time consumed for the whole experimental process. From these parameters, it can show the optimum level that produces the highest strength against tensile load. The best combination obtained from the result of Taguchi’s method for each parameter are Kenaf fibre, 55:45 fraction of volume ratio, and ‘Bisphenol A epoxy resin’ matrix (Miracast epoxy 1517). This composition gives the highest tensile stress value of 30.5 MPa.